2007
DOI: 10.5194/nhess-7-103-2007
|View full text |Cite
|
Sign up to set email alerts
|

Volcano Popocatepetl, Mexico: ULF geomagnetic anomalies observed at Tlamacas station during March–July, 2005

Abstract: Abstract. In this paper the first results of ULF (Ultra Low Frequency) geomagnetic anomalies observed at Tlamacas station (Long. 261.37, Lat. 19.07) located at 4 km near the volcano Popocatepetl (active volcano, Long. 261.37, Lat. 19.02) for the period March-July, 2005 and their analysis are presented. The geomagnetic data were collected with a 3-axial fluxgate magnetometer designed at UCLA (University of California, Los Angeles, 1 Hz sampling rate frequency, GPS). Our analysis reveals some anomalies which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
2
Order By: Relevance
“…Our earlier studies in the Popocatepetl Volcano area (2003)(2004)(2005)(2006) showed a variety of geomagnetic anomalies that were associated with volcano activity [Kotsarenko et al 2007] and also allowed us to propose the hypothesis of the existence of a second magmatic reservoir [Kotsarenko et al 2008]. The present study is devoted to various aspects of radon monotoring that was carried out in the first stage of our experimental investigations into the area of Popocatepetl Volcano (December 2007to December 2009.…”
Section: Special Issue: Earthquake Precursorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Our earlier studies in the Popocatepetl Volcano area (2003)(2004)(2005)(2006) showed a variety of geomagnetic anomalies that were associated with volcano activity [Kotsarenko et al 2007] and also allowed us to propose the hypothesis of the existence of a second magmatic reservoir [Kotsarenko et al 2008]. The present study is devoted to various aspects of radon monotoring that was carried out in the first stage of our experimental investigations into the area of Popocatepetl Volcano (December 2007to December 2009.…”
Section: Special Issue: Earthquake Precursorsmentioning
confidence: 89%
“…In the third part of the present study, we examine previously observed geomagnetic anomalies [Kotsarenko et al 2007] and enhanced thunderstorm activity, in terms of the lithosphere-atmosphere coupling caused by intensive radon release under specific conditions in the area of Tlamacas Mountain.…”
Section: Special Issue: Earthquake Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de dezenas de trabalhos publicados, nas últimas duas décadas, sobre ocorrências de sinais ULF precursores de terremotos e atividades vulcânicas ainda há um certo grau de incerteza sobre suas condições de existência e detecção. Vários são os motivos que contribuem para essa incerteza: raridade de ocorrência desse tipo de eventos; poucas redes de monitoramento existentes; falta de repetibilidade pela impossibilidade de repetição do fenômeno ou pela não detecção simultânea por sistemas de sensoreamento independentes; falta ou não utilização de ferramentas adequadas de processamento de sinais para detecção dos eventos; dificuldades de se separar eventos atmosféricos ou ionosféricos de eventos sísmicos ou vulcânicos, entre outros (Park, 1997, Zlotnicki et al 2006Kolar, 2010;Hayakawa et al 2007;Kotsarenko et al 2005 Essa base de monitoramento já possui um conjunto de sensoreamento de micro-sísmos, baseados em sensores de Emissão Acústica, instalado pelo Istituto Corbino, Roma. A base também possui sistema de monitoramento de emissão de gases, da CNEA.…”
Section: Introductionunclassified
“…Kotsarenko (kotsarenko@geociencias.unam.mx) Different long-term observatories on the electro-magnetic (EM) environment of volcanoes are studied in different countries with high volcano hazards (Currenti et al, 2005;Enomoto et al, 2006;Fujinawa et al, 2006;Hata et al, 2001;Kotsarenko et al, 2007), and reliable physical models for their interpretation are established (Kagiyama et al, 1995;Kopytenko and Nikitina, 2004). In terms of this, the main aim of our study was to analyze the geomagnetic data observed at the Tlamacas station, Popocatepetl, obtained during the period 2003-2006 in order to find anomalies which could be related to geodynamical processes produced by the volcano Popocatepetl.…”
Section: Introductionmentioning
confidence: 99%